Ultrasonic Atomization of Distilled Water - Gaete-Garreton, L; Vargas-Hernandez, y; Briceno-Gutierrez, D (Acoustical Society of America, 2018)
Experimental data on ultrasonic atomization of distilled water in a frequency range from 5 to 50 kHz are presented. A good agreement was found with the predictions of Rajan and Pandit [Ultrasonics 39, 235-255 (2001)] for the atomized primary drop size as a function of frequency. The correlation of atomization drop size for different frequencies is useful when producing nanoparticles, spray drying of suspensions, and covering of surfaces using different liquid products. Determining the displacement amplitude threshold for atomization at different frequencies is valuable in designing ultrasonic atomization systems. It is essential to measure the displacement amplitude of the atomizing surface rather that power applied to the transducer because the former is absolute while the latter depends on the efficiency of the transducer and other design parameters. As previous predictions for atomization threshold proved inaccurate, an empirical expression is proposed (based on the authors measurements) to predict the amplitude atomization threshold for the studied frequency range. © 2018 Acoustical Society of America.